Patterns for Interfacing between Logic Programs and Multiple Ontologies - Cruz‐Filipe, L.; Nunes, I.; Gaspar, G. (SciTePress, 2013)
Originally proposed in the mid-90s, design patterns for software development played a key role in object-oriented programming not only in increasing software quality, but also by giving a better understanding of the power and limitations of this paradigm. Since then, several authors have endorsed a similar task for other programming paradigms, in the hope of achieving similar benefits. In this paper we discuss design patterns for hybrid semantic web systems combining several description logic knowledge bases via a logic program. We introduce eight design patterns, grouped in three categories: three elementary patterns, which are the basic building blocks; four derived patterns, built from these; and a more complex pattern, the study of which can shed some insight in future syntactic developments of the underlying framework. These patterns are extensively applied in a natural way in a large-scale example that illustrates how their usage greatly simplifies some programming tasks, at the level of both development and extension. We work in a generalization of dl-programs that supports several (possibly different) description logics, but the results presented are easily adaptable to other existing frameworks such as multi-context systems.
Keywords: Design Patterns; Hybrid Semantic Web Languages; DI-programs